The mountain wolves of southwestern Manitoba - Locky, David (My University, 2002)
I first became interested in the wolves of southwestern Manitoba while conducting peatland research at Duck Mountain during the last two summers. At first all I saw were wolf tracks and scat along the logging roads, but then I began to find the remains of ungulates, usually moose that had been taken by wolves in the forested peatlands. On lucky days, the silence of hot summer afternoons was broken by the howls of wolf pups and once two adults called very close to the camp. These experiences fueled a long-time fascination with wolves and I embarked on a quest to discover more about the wolves in the region. My search led me over Duck Mountain and south to Riding Mountain National Park and the results have revealed a remarkable story of the mountain wolves of southwestern Manitoba.
Keywords: wolves; Manitoba